GROUND WATER LEVEL LOWERING ESTIMATION BASED ON TIME-LAPSE MICRO-GRAVITY AND SUBSIDENCE DATA IN SEMARANG ALLUVIAL PLAIN - ARI PRIHANDOKO , EKO
High precision gravity surveys called time-lapse micro-gravity were repeatedly conducted on an alluvial sedimentation system in Semarang area. The purpose of measurement of gravity anomaly, elevation and change in well data depth are to understand the characteristic of gravity anomaly and land subsidence in the interest area, so the estimation in ground water level lowering is ascertainable. Analysis in alteration of gravity anomaly and subsidence response can be used to make a model that show ground water level lowering trend in the interest area. Measurements of micro-gravity were conducted over July 2002 until November 2005 in rainy and dry season. Data used in calculations and interpretation consist of time-lapse micro-gravity anomaly data, elevation data (subsidence data) and observe well data profile which shows the change of ground water level depth. Correlation technique had been done toward the subsidence and time-lapse gravity data to support analysis and interpretation of land subsidence and ground water level lowering. The change of ground water level lowering model is based on the calculations in Gaussian integration that produce a thickness change for ground water level lowering that controlled by hydrology data in the interest area.